2009
DOI: 10.1111/j.1463-1326.2008.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

RBP‐to‐retinol ratio, but not total RBP, is elevated in patients with type 2 diabetes

Abstract: Our results suggest that the excess of RBP relative to retinol, assessed as the RBP-to-retinol ratio, is more indicative of T2DM than RBP itself. Hence, the previously reported insulin resistance in mice induced by overexpression or injection of RBP could be because of higher levels of RBP relative to retinol rather than higher total levels of RBP. Moreover, TNF-alpha may have a role in RBP-mediated adipose to muscle crosstalk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
70
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 38 publications
14
70
0
1
Order By: Relevance
“…BCMO1 is known to accelerate conversion of b-carotene to retinol during insulin resistance states, which to some extent explains the observed high levels of plasma retinol in these rats (25). However, in some studies, plasma RBP4 levels were reported to be in excess of retinol, and elevated RBP4/retinol ratio is found to be a better predictor of insulin resistance rather than RBP4 levels alone (11,26). As binding of retinol is an absolute necessity for RBP4 secretion from tissues (3), it is possible that increased tissue uptake of RBP4-retinol complex might lead to transient elevation of plasma apo-RBP4 levels.…”
Section: Plasma Rbp4 Ttr and Retinol Levels In Type 2 Diabetesmentioning
confidence: 98%
“…BCMO1 is known to accelerate conversion of b-carotene to retinol during insulin resistance states, which to some extent explains the observed high levels of plasma retinol in these rats (25). However, in some studies, plasma RBP4 levels were reported to be in excess of retinol, and elevated RBP4/retinol ratio is found to be a better predictor of insulin resistance rather than RBP4 levels alone (11,26). As binding of retinol is an absolute necessity for RBP4 secretion from tissues (3), it is possible that increased tissue uptake of RBP4-retinol complex might lead to transient elevation of plasma apo-RBP4 levels.…”
Section: Plasma Rbp4 Ttr and Retinol Levels In Type 2 Diabetesmentioning
confidence: 98%
“…Methodological differences in collection of the samples and determination of RBP4 levels must be considered (32). Confounding effects of retinol status, iron status, and kidney function also seem to be of importance and should be addressed in the design of future studies (22,26,78). Additional studies on human adipocytes are needed to unravel the regulation of RBP4 expression and secretion and its auto-and para-crine effects.…”
Section: Discussionmentioning
confidence: 99%
“…It transports retinol from the liver to the peripheral tissues (21). Plasma RBP4 levels positively correlate with retinol levels (22). Therefore, subject's retinol status can influence circulating RBP4 levels.…”
Section: Characteristics Of Rbp4mentioning
confidence: 99%
See 2 more Smart Citations